Investigating the Importance of Context in the Analysis and Interpretation of Ogundimu’s A Silly Season - DADJO, Servais Dieu-Donné Yédia (My University, 2021)
This paper investigates the importance of context in the analysis and interpretation of Ogundimu‟s A Silly Season. It aims to describe, analyse and interpret linguistic context, situational context, and cultural context of the production of speech events in A Silly Season. Basing on a descriptive survey method relevant passages that require the clarification of contexts for their full understanding have been selected. It has been contended that the description of the linguistic context of the highlighted lexical items has helped determine who the speakers and hearers are in terms of the roles they have played either individually or collectively. In the same way, the description of the situational context clarifies the circumstances in which the speech events take root and even helps disambiguate ambiguous sentences. The description of the cultural context of words and expressions used has helped contend that the author values Yoruba culture and tradition.
Keywords: Cultural context; linguistic context; situational context; lexical items